Pengungkapan Akuntansi Sumber Daya Manusia dan Kinerja Keuangan Perusahaan - Sri Suranta; Faiz Alafi S. (Jurnal Akuntansi, 2018)
The purpose of this study is to empirically examine about the correlation between human resource accounting disclosure and the Company’s financial performance. The human resource accounting disclosure is measured by using an index that developed by Syed Mamun (Bangladesh) that consists 16 items. Meanwhile the company’s financial performance is proxied by Return on Asset (ROA), Asset Turn Over (ATO), and Market to Book Value (MBV). This Study is using secondary data that are insurance and financial company who listed in Indonesia Stock exchange at 2013-2015. The final sample in this study are 69 companies. The method that used in sample choosing is purposive sampling. The analytical methods that used consist descriptive analysis to determine the description of the research data, test of normality to determine the normality of data and the linearity test to show the linearity of data, and Pearson Product Moment correlation test that used to test the hypotheses in this study. The result of this study show that human resource accounting disclosure in Indonesia is classified high than other developing country, sucs as Bangladesh, Nigeria and India. The result of correlation testing show that human resource accounting disclosure has a positive correlation on ROA, ATO, and MBV. Keywords: human resource accounting disclosure, financial performance